2020
DOI: 10.1002/etc.4819
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dietary Exposure to Coal Ash Contaminants within Food Ration on Growth and Reproduction in Daphnia magna

Abstract: Coal ash contains numerous contaminants and is the focus of regulatory actions and risk assessments due to environmental spills. We exposed Daphnia magna to a gradient of coal ash contamination under high and low food rations to assess the sublethal effects of dietary exposures. Whereas exposure to contaminants resulted in significant reductions in growth and reproduction in daphnids, low, environmentally relevant food rations had a much greater effect on these endpoints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 61 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…It is always complex to address the risks associated with trace elements on aquatic biota based solely on their concentrations because many factors can significantly affect trace element bioavailability and toxicity and, therefore, the consequences on the invertebrate populations (e.g., Mathews et al 2020). However, it is interesting to note that Mebane et al (2020) showed that mayflies were species‐sensitive to trace elements and that their distribution could be strongly influenced by the concentrations of trace elements such as Cd, Cu, Ni, and Zn, alone or in mixture.…”
Section: Discussionmentioning
confidence: 99%
“…It is always complex to address the risks associated with trace elements on aquatic biota based solely on their concentrations because many factors can significantly affect trace element bioavailability and toxicity and, therefore, the consequences on the invertebrate populations (e.g., Mathews et al 2020). However, it is interesting to note that Mebane et al (2020) showed that mayflies were species‐sensitive to trace elements and that their distribution could be strongly influenced by the concentrations of trace elements such as Cd, Cu, Ni, and Zn, alone or in mixture.…”
Section: Discussionmentioning
confidence: 99%